(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Cervical Spondylosis is a common spinal problem now days. It is a general term for age related wear and tear affecting spinal disc of the neck. Normally soft disc between vertebras provides cushioning, with Cervical Spondylosis the disc becomes compressed, when this happens the cartilage can wear away. Once this protective cartilage is gone, spur may develop on your vertebrae where they rub together and the nerves attached to spinal cord will have less room to pass between the vertebras. Cervical Spondylosis usually starts earlier in men than women. Usually it doesn’t lead to disability but sometimes these changes in the spine can cause compression which makes the finger clumsy. In Karnataka incidence and prevalence is 7.25 cases per 1000 populations and in Bangalore prevalence of Cervical Spondylosis is 23.25 per 10000 populations. Cervical Spondylosis can be compared to Manyasthambha mentioned in the classics. Divaswapna, Asamasthana, Vivrutho Urva nirikshana are the main causes leading to Manyasthambha. Ruk and Sthambha are the main Lakshanas of Manyasthambha. Considering these Lakshanas along with radiation of pain and Motor activity as the assessment parameters, Nasya Karma and Swedana were adopted in the study, which showed highly significant result in almost all parameters with p value < 0.001 taken for assessment in the group.